Association of implementation of a public bicycle share program with intention and self-efficacy: The moderating role of socioeconomic status. (June 2016) - Bélanger-Gravel, Ariane; Gauvin, Lise; Fuller, Daniel; Drouin, Louis
This natural experiment examines the effect of a public bicycle share program on cognitions and investigates the moderating influence of socioeconomic status on this effect. Two cross-sectional population-based surveys were conducted. Intention and self-efficacy to use the public bicycle share program were assessed by questionnaire. A difference-in-differences approach was adopted using logistic regression analyses. A significant effect of the public bicycle share program was observed on intention (exposure × time; odds ratio = 3.41; 95% confidence interval: 1.50–7.73) and self-efficacy (exposure; odds ratio = 1.61; 95% confidence interval: 1.28–2.01). A positive effect on intention was observed among individuals with low income (exposure × time; odds ratio = 27.85; 95% confidence interval: 2.51–309.25). Implementing a public bicycle share program is associated with increases in intention and self-efficacy for public bicycle share use, although some social inequalities persist.